Produksi Kotoran Cacing Tanah dan Hubungannya dengan Kelimpahan Cacing Tanah pada Ekosistem Alami dan Ekosistem Buatan - Regina Jody; Darmi Darmi; Rizwar Rizwar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The presence of earthworms in an ecosystem can improve soil quality through physical, chemical and biological properties. The activity of earthworms in producing feces also has an important role in increasing soil fertility. This research aims to analyze the production of earthworm feces and its relationship with the abundance of earthworms in natural and artificial ecosystems. Determining location points uses the Cluster Sampling method, namely natural and artificial ecosystems. Sampling of earthworms and their feces used the line transect method with a length of 100 meters and plots were created along the transect lines to observe the population and production of earthworm feces with 20 replicate plots at each location. Data analysis includes average feces weight, number of earthworm feces, and correlation analysis. Morphological data on earthworm droppings were analyzed descriptively. The results of this research show that in natural ecosystems there are 2 forms of earthworm feces, namely granular and globular types, whereas in artificial ecosystems there is only 1 form of earthworm feces, namely globular. Earthworm feces production is higher in natural ecosystems than in artificial ecosystems. The relationship between dung production (number of deposits and weight of dung deposits) of earthworms with the number and biomass of earthworms shows a significant relationship with a moderate correlation category (<1), while the relationship between earthworm density and worm biomass correlates significantly with a strong correlation category (1).